Pengaruh Kepribadian terhadap Komitmen Organisasi dan Perilaku serta Kinerja Karyawan pada Perusahaan Perkayuan di Jawa Timur - Koesmono, H. Teman (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2004)
The purpose of this research is to find out how big is the effect of personality toward organization commitment behavior and employee's job performance, especially on the supervisor level in the production area. The analytical until is the employee which is the supervisor in production area of sub sector in wood industry in East Java.